Hubungan Dukungan Keluarga dengan Kemandirian Lansia dalam Memenuhi Aktivitas Kehidupan Sehari-hari di Desa Tonusu Kecamatan Pamona Puselemba Kabupaten Poso - Djala, Fany Lairin; Gugu, Arwin (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Background: Elderly is someone aged 60 years and over. The elderly experience changes in the form of decreased organ function so that the elderly have difficulty in fulfilling daily activities. Elderly independence in daily activities can be measured by the Katz Index. In this era of globalization, families are busy with their respective jobs so that they pay less attention to or provide support to the elderly. Objective: to determine the relationship between family support and independence of the elderly in fulfilling activities of daily life in Tonusu Village, Pamona Puselemba District, Poso Regency. Methods: The type of research used is descriptive analytic with a cross-sectional approach. The sample used is 50 respondents using simple random sampling technique. Data collection was done by using a questionnaire. Results: showed that there was a relationship between emotional support and the independence of the elderly in fulfilling daily activities with a p value = 0.000, there was a relationship between instrumental support and the independence of the elderly in fulfilling daily activities (p value = 0.000), there was a relationship between assessment support and the independence of the elderly. in fulfilling daily activities (p value = 0.002), there is a relationship between informational support and the independence of the elderly in fulfilling daily activities (p value = 0.000), Conclusion: It can be concluded that there is a relationship between family support and elderly independence in fulfilling activities of daily life in Tonusu Village, Pamona Puselemba Subdistrict, Poso RegencyÂ Keyword :Family support, Elderly independence